Germinated brown rice alters Aβ(1-42) aggregation and modulates Alzheimer's disease-related genes in differentiated human SH-SY5Y cells - Azmi, Nur Hanisah; Ismail, Maznah; Ismail, Norsharina; Imam, Mustapha Umar; Mohamed Alitheen, Noorjahan Banu; Abdullah, Maizaton Atmadini (Hindawi Publishing Corporation, 2015)
The pathogenesis of Alzheimer’s disease involves complex etiological factors, of which the deposition of beta-amyloid (Aβ) protein and oxidative stress have been strongly implicated. We explored the effects of H2O2, which is a precursor for highly reactive hydroxyl radicals, on neurotoxicity and genes related to AD on neuronal cells. Candidate bioactive compounds responsible for the effects were quantified using HPLC-DAD. Additionally, the effects of germinated brown rice (GBR) on the morphology of Aβ(1-42) were assessed by Transmission Electron Microscopy and its regulatory effects on gene expressions were explored. The results showed that GBR extract had several phenolic compounds and γ-oryzanol and altered the structure of Aβ(1-42) suggesting an antiamyloidogenic effect. GBR was also able to attenuate the oxidative effects of H2O2 as implied by reduced LDH release and intracellular ROS generation. Furthermore, gene expression analyses showed that the neuroprotective effects of GBR were partly mediated through transcriptional regulation of multiple genes including Presenilins, APP, BACE1, BACE2, ADAM10, Neprilysin, and LRP1. Our findings showed that GBR exhibited neuroprotective properties via transcriptional regulation of APP metabolism with potential impact on Aβ aggregation. These findings can have important implications for the management of neurodegenerative diseases like AD and are worth exploring further.